Output Distortions and the Choice of Legal Form of Organization - Katarzyna Anna Bilicka; Sepideh Raei (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study the distortions to aggregate output created by the differential tax treatment of corporations and pass through entities. We develop an industry equilibrium model in which the legal form of organization is an endogenous choice for firms facing trade off between tax treatment of business income, access to external capital, and the evolution of productivity over time. We match this model to features of the US economy. We find that, relative to the benchmark economy, revenue-neutral tax reform in which legal forms receive the same tax treatments leads to 1.25% increase in the aggregate output.
Keywords: E62; H32; H25; 330; output distortions; legal form of organization; pass through